Bridging the Digital Divide: A Case Study of a Low-Bandwidth Mobile Language Learning Initiative in Eastern Indonesia - Thandeka Mhlanga; Rina Farah; Zara Ali (International Journal of Language and Ubiquitous Learning, 2026)
Digital inequities remain a critical barrier to language learning opportunities in remote and underserved regions, particularly where internet connectivity is unstable and infrastructure is limited. Low-bandwidth mobile learning solutions offer a promising alternative for supporting equitable access to instructional resources, yet empirical evidence on their effectiveness in real-world settings remains limited. This study aims to examine how a low-bandwidth mobile language learning initiative implemented in an Eastern Indonesian community supports learner engagement, accessibility, and linguistic development. A qualitative case study methodology was employed, involving 32 secondary school learners, three local teachers, and two community facilitators. Data were collected through mobile usage analytics, classroom observations, semi-structured interviews, and learner performance tasks adapted for low-data environments. The findings indicate that the initiative substantially improved access to learning materials, increased learner motivation, and supported incremental gains in vocabulary acquisition and basic communicative competence. Learners reported that offline-capable modules, audio-light exercises, and text-based microtasks reduced frustration associated with poor connectivity and enabled more consistent participation. Teachers highlighted the importance of culturally contextualized content and community support in sustaining engagement. The study concludes that low-bandwidth mobile learning can help bridge the digital divide when paired with context-sensitive pedagogical design and local capacity-building. Further research is recommended to explore scalability, long-term learning outcomes, and policy frameworks that could strengthen digital inclusion in remote regions.